Silencing long non-coding RNA ROR improves sensitivity of non-small-cell lung cancer to cisplatin resistance by inhibiting PI3K/Akt/mTOR signaling pathway - Hui Shi; Jin Pu; Xiao-Li Zhou; Yun-Ye Ning; Chong Bai (Tumor Biology, 2017)
This study aimed to investigate the effects of long non-coding RNA ROR (regulator of reprogramming) on cisplatin (DDP) resistance in patients with non-small-cell lung cancer by regulating PI3K/Akt/mTOR signaling pathway. Human cisplatin-resistant A549/DDP cell lines were selected and divided into control group, negative control group, si-ROR group, ROR over-expression group, Wortmannin group, and ROR over-expression + Wortmannin group. MTT assay was used to determine the optimum inhibitory concentration of DDP. Quantitative real-time polymerase chain reaction and western blotting were applied to detect expressions of long non-coding RNA ROR, PI3K, Akt, and mTOR. Colony-forming assay, scratch test, Transwell assay, and flow cytometry were conducted to detect cell proliferation, migration, invasion, and apoptosis, respectively. Tumor-formation assay was performed to detect the growth of transplanted tumors. Long non-coding RNA ROR expression was high in human A549/DDP cell lines. Compared with the control and negative control groups, the mRNA and protein expressions of PI3K, Akt, mTOR, and bcl-2 decreased, whereas the mRNA and protein expression of bax and the sensitivity of cells to DDP significantly increased. Cell proliferation, migration, and invasion abilities decreased in the si-ROR and Wortmannin groups. In comparison with control and negative control groups, the mRNA and protein expressions of PI3K, Akt, mTOR, and bcl-2 increased, whereas the mRNA and protein expressions of bax decreased, the sensitivity of cells to DDP significantly increased, and cell proliferation, migration, and invasion abilities decreased in the ROR over-expression group. For nude mice in tumor-formation assay, compared with control and negative control groups, the tumor weight was found to be lighter (1.03 ± 0.15) g, the protein expressions of PI3K, Akt, mTOR, and bcl-2 decreased, and the protein expression of bax increased in the si-ROR group. Long non-coding RNA ROR may affect the sensitivity of lung adenocarcinoma cells to DDP by targeting PI3K/Akt/mTOR signaling pathway.